2016
DOI: 10.1177/0271678x16665623
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral testing in subarachnoid hemorrhage: A review of methods and current findings in rodents

Abstract: The most important aspect of a preclinical study seeking to develop a novel therapy for neurological diseases is whether the therapy produces any clinically relevant functional recovery. For this purpose, neurobehavioral tests are commonly used to evaluate the neuroprotective efficacy of treatments in a wide array of cerebrovascular diseases and neurotrauma. Their use, however, has been limited in experimental subarachnoid hemorrhage studies. After several randomized, double-blinded, controlled clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 153 publications
0
24
1
Order By: Relevance
“…Sham-operated controls received the same procedure without inserting the filament. Animals were recovered for 24 hours, then all rats were assessed with the standard 5-point neuroscore scale to evaluate neurological outcomes 11 . CSF (at least 50 μL per rat) was collected from the cisterna magna for JC1 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Sham-operated controls received the same procedure without inserting the filament. Animals were recovered for 24 hours, then all rats were assessed with the standard 5-point neuroscore scale to evaluate neurological outcomes 11 . CSF (at least 50 μL per rat) was collected from the cisterna magna for JC1 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative prognosis, using Russell and Smith’s classification, is divided as severe or very severe [ 8 ]. Considering that detailed classification helps to determine the severity of injury, informs treatment options and is used to assess prognosis and functional recovery, recent suggestions have indicated that better diagnostic and assessment criteria are needed in the TBI field [ 9 , 10 ].…”
Section: Types Of Traumatic Brain Injuries In Humansmentioning
confidence: 99%
“…EBI occurs in 12% of patients after SAH and is caused by a combination of transient global ischemia associated with abrupt increase in intracranial pressure plus the toxic effects of blood in the subarachnoid space. It is characterized by neuroinflammation, blood–brain barrier (BBB) disruption, cerebral edema, and neuronal cell death . DCI occurs in ~30–40% of patients after SAH, is multifactorial in etiology, and is characterized by delayed onset of ischemic neurological deficits and/or radiographic evidence of cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%